The Influence of Leaf Fertilizer Media on Multiplication of Barangan Banana (Musa acuminate L.) in vitro - Liberty Chaidir; Dina Nur Mardiana; Ahmad Taofik; Yati Setiati Rachmawati (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Barangan banana (Musa acuminata L.) is a plant that has the biggest contribution to national fruit production. The increasing demand for the banana requires the availability of seedlings, while conventional cultivation is unable to produce healthy, disease-free seedlings in a short time and large amount. In vitro culture is considered to be able to handle the constraints of the conventional seed supply.  The purpose of this study was to determine the effect of foliar fertilizers on in vitro multiplication of barangan bananas. The method used was a single factor of Completely Randomized Design (CRD), the addition of leaf fertilizer consisting of five levels of media treatment, media MS (control), and 0.50 ml L-1 (p1); 0.75 ml L-1 (p2); 1.00 ml L-1 (p3); 1.25 ml L-1 (p4); 1.50 ml L-1 (p5) of leaf fertilizer media repeated five times. The data were analyzed with Analysis Variance then followed by Duncan Multiple Ranged Test of 5%. The results showed MS media still gave the best results compared to other leaf fertilizer media. Meanwhile, the leaf fertilizer media used in this study still gave good results on the initial time of buds appearance (p3 treatment), the number of shoots and the number of leaves in the p5 treatment, as well as the height of the plant in the p4 and p5 treatments. Therefore, the leaf fertilizer can be used to substitute MS media